Case Report: Toxic epidermal necrolysis induced by sintilimab in a patient with advanced lung squamous cell carcinoma - Wu, Jiaxing; Hu, Mingjun; Chen, Juan; Wang, Qingqun; Wang, Ailing; Mao, Wanli (Frontiers in Pharmacology, 2026)
BackgroundSintilimab is an effective PD-1 immune checkpoint inhibitor (ICI) for advanced non-small cell lung cancer (NSCLC). However, it can cause severe immune-related adverse events (irAEs) such as toxic epidermal necrolysis (TEN), a rare hypersensitivity reaction with significant mortality. Reports of Sintilimab-induced TEN are exceedingly rare, making its recognition and management crucial.Case summaryA 60-year-old female with advanced NSCLC developed TEN 3 days after her second dose of Sintilimab. The condition progressed rapidly, with epidermal detachment affecting 85% of her body surface area (BSA). Immediate interventions, including high-dose corticosteroids, intravenous immunoglobulin, meticulous wound care, and infection control, led to gradual recovery. After 39 days of intensive care, the patient was discharged with complete healing of skin lesions and no significant complications.ConclusionThis report highlights the potential for Sintilimab to induce life-threatening TEN, emphasizing the need for vigilant monitoring and prompt intervention during ICIs therapy.